Penyimpangan Seksual: Sebuah Interpretasi Teologi, Psikologi dan Pendidikan Islam - Masmuri Masmuri; Syamsul Kurniawan (PSGA LP2M IAIN Pontianak, 2016)
Sexual deviance, sexual abnormality, or sexual violence is behavioral force to gain a sexual pleasure from sexual objects or in a peculiar way. In this context, the sexual deviance is clearly against the humanity and the common sense. This issue would be discussed thoroughly by the writers. Besides, the main focus of this writing is the sexual deviance which is limited by theological, psychological, and Islamic education interpretation.